Phosphodiesterase-4 Inhibition in the Management of Psoriasis - Erika L. Crowley; Melinda J. Gooderham (MDPI AG, 2023)
Psoriasis is a common chronic immune-mediated disease with many comorbidities and impacts on quality of life. Among the treatments for psoriasis, phosphodiesterase-4 (PDE4) inhibitors are emerging with expanding options. PDE4 inhibitors play a pivotal role in the inflammatory cascade by degrading cyclic adenosine monophosphate (cAMP), contributing to pro-inflammatory mediator production. Apremilast, an oral PDE4 inhibitor, is approved for psoriasis. While effective, its adverse effects can limit its utility. Roflumilast, a topical PDE4 inhibitor, was also recently approved for psoriasis and shows promise in clinical trials. Crisaborole, a PDE4 inhibitor approved for atopic dermatitis, has also been studied in psoriasis. This review summarizes evidence from randomized clinical trials regarding the efficacy and safety of PDE4 inhibitors in psoriasis treatment. By highlighting their potential benefits and limitations, this review provides valuable insights for clinicians and researchers aiming to optimize psoriasis management.